Influence of pulsed direct current on the growth rate of intermetallic phases in the Ni–Al system during reactive spark plasma sintering. (15th July 2022) - Abedi, Mohammad; Asadi, Atefeh; Sovizi, Saeed; Moskovskikh, Dmitry; Vorotilo, Stepan; Mukasyan, Alexander
Abstract: The effect of pulsed direct current (PDC) on solid-state diffusion in the Ni–Al binary system was investigated. Two experimental schemes were employed: in the presence and absence of an electric field. The diffusion couples were heat-treated for 1.5, 3, and 5 h at 803, 833, and 863 K. Under the investigated conditions, only two intermetallic phases (NiAl3 and Ni2 Al3 ) formed at the boundary of the metals. It was shown that the PDC passing through the diffusion couple significantly enhanced the growth rates of both phases. The apparent reaction–diffusion coefficients were D NiA l 3 = 4.0 × 10 − 9 exp ( − 7.6 × 10 4 RT ) and D N i 2 A l 3 = 9.7 × 10 − 9 exp ( − 8.4 × 10 4 RT ) in the field-assisted scheme, whereas their corresponding values in the field-insulated scheme were D NiA l 3 = 6.1 × 10 − 5 exp ( − 1.55 × 10 5 RT ) and D N i 2 A l 3 = 3.7 × 10 − 4 exp ( − 1.71 × 10 5 RT ) . The results directly imply that the effective activation energy of diffusion decreases by approximately two times when the PDC passes through the media. Graphical abstract: Image, graphical abstract